2022
DOI: 10.21037/jtd-22-1162
|View full text |Cite
|
Sign up to set email alerts
|

Ninety-seven cases of experiences with the left thoracotomy approach for off-pump conventional revascularization: a retrospective cohort study

Abstract: Background: Minimally invasive coronary surgery-coronary artery bypass grafting (MICS CABG) is well adopted in clinical practice. However, this procedure did not really achieve conventional complete revascularization. The present study aimed to explore the feasibility and safety of conventional revascularization via the left thoracotomy (8-10 cm) approach.Methods: From January 2020 to March 2022, a total of 97 consecutive patients who needed coronary artery revascularization were operated on using this techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…However, as mentioned above, no study has examined the safety of MICSOPCAB in patients with impaired LV function; therefore, whether low EF should be included in patient selection is still unclear. In the present series, MICSOPCAB showed significant differences in the ICU stay (2 [1][2] in the Low EF group vs. 1 [1][2] in the Normal EF group; p = 0.010) and perioperative transfusions (69.7% in the Low EF group vs. 49.2% in the Normal EF group; p = 0.023) but did not compromise hospital stay or complication rates in patients with low EF, comparable to other recent studies (1,2,4,17). Based on the results of the present study, we advocated that low EF should not be identified as an absolute contraindication for MICSOPCAB.…”
Section: Conventional Opcab Via Median Sternotomy Vs Micsopcab In Pat...supporting
confidence: 88%
See 2 more Smart Citations
“…However, as mentioned above, no study has examined the safety of MICSOPCAB in patients with impaired LV function; therefore, whether low EF should be included in patient selection is still unclear. In the present series, MICSOPCAB showed significant differences in the ICU stay (2 [1][2] in the Low EF group vs. 1 [1][2] in the Normal EF group; p = 0.010) and perioperative transfusions (69.7% in the Low EF group vs. 49.2% in the Normal EF group; p = 0.023) but did not compromise hospital stay or complication rates in patients with low EF, comparable to other recent studies (1,2,4,17). Based on the results of the present study, we advocated that low EF should not be identified as an absolute contraindication for MICSOPCAB.…”
Section: Conventional Opcab Via Median Sternotomy Vs Micsopcab In Pat...supporting
confidence: 88%
“…Regarding multivessel arterial grafting, MICSOPCAB is also evolving. Harvesting bilateral internal mammary arteries via left small thoracotomy has been challenging; however, their safety has improved in recent years (4,17). This study used bilateral internal mammary arteries in 15 patients.…”
Section: Conventional Opcab Via Median Sternotomy Vs Micsopcab In Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of surgical revascularization through a left thoracic minimal incision stepped up from single bypasses to multiple bypasses with total arterial grafting using BITA ( 3 , 14 , 15 ). Kikuchi and colleagues analyzed short-term outcomes of MICS-OPCAB using BITA and a single internal thoracic artery (SITA) at a single Japanese medical center between February 2012 and December 2015 ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive direct coronary artery bypass grafting (MIDCAB) ( 1 ) was popularized in the 1990s. Nowadays, multivessel coronary artery bypass grafting (CABG) via a left small thoracotomy has developed as a minimally invasive cardiac surgery coronary artery bypass (MICS-CABG) and maintained gaining attention ( 2 , 3 ). In our institution, we have performed off-pump coronary artery bypass (OPCAB) as a standard procedure, and patients with favorable coronary anatomy and condition are selected for MICS-OPCAB.…”
Section: Introductionmentioning
confidence: 99%